Ex-vivo normothermic liver perfusion: an update. - Vogel, T; Brockmann, J; Friend, P (2010)
PURPOSE OF REVIEW: There is increasing disparity between the supply of acceptable donor organs and the number of potential transplant recipients. The shortage of organs for transplantation demands optimal utilization of a wider spectrum of donor organs, including nonheart-beating and other extended criteria donors. In the case of the liver, a substantial number of organs are discarded because of a risk of primary nonfunction. RECENT FINDINGS: For many years hypothermic preservation has been the universal standard for organ preservation. Although limited in terms of the duration of preservation it has had the major advantages of simplicity, portability and affordability. Organ preservation by normothermic machine perfusion has repeatedly proven superiority over static cold storage in experimental settings. However, it is complex and costly and its place in clinical transplantation has not yet been established. In liver preservation normothermic perfusion provides the potential: (a) to preserve extended criteria grafts for long periods; (b) to assess the viability of these grafts during perfusion; and (c) to improve the condition of the grafts. SUMMARY: Avoidance of cold ischaemic preservation damage and repair of injury sustained during warm ischaemia and organ procurement would potentially allow many livers from extended criteria donors to be transplanted reliably. The current challenges are, first to confirm the feasibility of the normothermic machine perfusion methodology in human livers and, second, to develop and introduce a functional device into the clinical arena.